CASTLE Thyroid Tumor: A Case Report and Literature Review - Lominska, Chris; Estes, Christopher Fleighton; Neupane, Prakash C.; Shnayder, Y.; TenNapel, Mindi J.; O’Neil, Maura F. (Frontiers in Oncology, 2017)
Carcinoma showing thymus like differentiation is a rare tumor of the thyroid gland which is structurally similar to thymic tissue. Overall, it has a favorable prognosis. Radiotherapy has been shown to be an effective local treatment, but there have been reports of distant recurrence. It has been suggested that adding chemotherapy may decrease the risk of recurrence. Here, we present a case report of a patient with a large tumor and extrathyroidal extension. The patient was treated with surgery, radiotherapy, and cisplatin with acceptable toxicity. The patient is free of locally recurrent or distant disease at 3 years.